Agricultural Economics Research. (Washington, D.C. Economic Research Science, U.S. Department of Agriculture, 1949)
Contains articles on the production and marketing of major agricultural commodities; foreign agriculture and trade; economic use, conservation, and development of natural resources; trends in rural population, employment, and housing; rural economic adjustment problems; and performance of the U.S. agricultural industry.
Quarterly